The Damascus document : a centennial of discovery : proceedings of the third International Symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature, 4-8 February 1998 - Baumgarten, Joseph M.; Chazon, Esther G.; Pinnick, Avital. (Studies on the Texts of the Desert of Judah, 1999)
The papers published in this volume were presented at the Third International Orion Symposium (1998), to mark the centennial of the discovery of the Damascus Document (CD) in the Cairo Geniza and the final publication of the 4QD manuscripts in the Discoveries in the Judaean Desert series. Since its discovery, CD has sparked lively debate about its sectarian origins and halacha, issues with far-reaching implications not only for the development of Jewish law but also for the very nature of Second Temple period Judaism and its continuity into the early medieval period. The contributors examine the physical reconstruction of CD, its relationship to other legal works in the Qumran corpus and to rabbinic law. Essays on specific legal topics, as well as historical perspectives, round out the volume.